2009
DOI: 10.1021/jf901367u
|View full text |Cite
|
Sign up to set email alerts
|

LDL Oxidation, Antioxidant Capacity and Growth of Cultured Grey Mullet (Mugil cephalus) Fed Dietary Sorghum Distillery Residue Pretreated with Polyethylene Glycol

Abstract: Dietary sorghum distillery residue (SDR) showed antioxidant and blood thinning effects on grey mullet during winter, but inhibited their growth. The objective of this study was to establish a preliminary treatment of the dietary SDR with polyethylene glycol (PEG), a tannin-binding agent, to enhance growth and blood antioxidant capacity of grey mullet ( Mugil cephalus ) feed. The feeding trial was carried out from June to November. The water temperature was between 25 and 30 degrees C; the specific growth rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…6 A grey mullet fed diet containing 20% SDR resulted in significantly increased total antioxidant capacity of blood plasma and prolonged the lag phase of ex vivo tilapia LDL oxidation compared to those fed the control diet. 5 SDR extracts were found to have free-radical-scavenging and tyrosinase-inhibiting effects. 5,7 Both in vitro and ex vivo LDL oxidation of tilapia were inhibited by the hot-water extract of freshwater clam in a similar dose-dependent pattern.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A grey mullet fed diet containing 20% SDR resulted in significantly increased total antioxidant capacity of blood plasma and prolonged the lag phase of ex vivo tilapia LDL oxidation compared to those fed the control diet. 5 SDR extracts were found to have free-radical-scavenging and tyrosinase-inhibiting effects. 5,7 Both in vitro and ex vivo LDL oxidation of tilapia were inhibited by the hot-water extract of freshwater clam in a similar dose-dependent pattern.…”
Section: ■ Introductionmentioning
confidence: 99%
“…3 The antioxidative properties of polyphenols allow them to suppress low-density lipoprotein (LDL) oxidation and scavenge free radicals. 4,5 Polyphenols demonstrate antioxidative activities better than vitamin C and vitamin E 4 . Grey mullet (Mugil cephalus) fed SDR improved blood fluidity and cold adaptation during winter.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, this study might suggest that flavonoids improve the antioxidant response in Nile tilapia liver under induced stress. On the other hand, Lee et al [ 92 ] indicated that the dietary inclusion of residues from the distillation of sorghum (200 g/kg), increases the antioxidant activity and delays the oxidation process of low-density lipoproteins in the plasma of the Lysa ( Mugil cephalus ). Among the main bioactive compounds present in sorghum are phenolic acids (caffeic, ferulic and chlorogenic acids) and flavonoids (apigeninidin, luteolinidin, and naringenin), which have been directly related to its antioxidant activity [ 93 ].…”
Section: Use Of Bioactive Compounds From Agro-industrial Waste In mentioning
confidence: 99%
“…The addition of SDR in chicken forage increases the antioxidant activities of animal organs without affecting their final body weight (Lee et al . ; Hsin et al . ).…”
Section: Introductionmentioning
confidence: 96%
“…The addition of SDR in chicken forage increases the antioxidant activities of animal organs without affecting their final body weight Hsin et al 2011). However, studies have also reported the inhibitory effect of SDR on the growth of grey mullet, cattle, chicken and rats (Larraín et al 2009;Lee et al 2009).…”
Section: Introductionmentioning
confidence: 99%